Application of Chitosan Edible Coating Using Dip and Spray Method on Postharvest Quality of Cavendish Banana - Ulya, Putri Rutbata; Palupi, Nurheni Sri; Pramuhadi, Gatot (Teknotan: Jurnal Industri Teknologi Pertanian, 2025)
Applying postharvest technologies such as edible coatings is one of effective method to extend the shelf life of bananas. Chitosan, an edible biopolymer, has excellent film-forming properties that allow it to coat fruit surfaces and prolong freshness. The coating method plays a crucial role in the effectiveness of edible coatings. This study aimed to evaluate the effect of coating method on the postharvest quality of Cavendish bananas through statistical analysis. In this research, 1.25% chitosan solution was applied using two methods: dipping and spraying, with uncoated bananas serving as the control. A knapsack power sprayer was used to apply the coating solution in the spray treatment. Bananas were stored at room temperature (26 ± 2°C) and 80 ± 5% relative humidity for 11 days. Results showed that spray-coated bananas experienced the lowest weight loss (14.51%) and disease severity score (3.33), highest value in L* (53,88), b* (30,97), pH (5,82) and pulp-to-peel ratio (2,57), firmest texture (28,06 mm/150g/5sec) along with slowest starch conversion (45%) by day-5. In comparison, dip-coated bananas lost 15.32% weight, highest TSS value (15,87), 65% degraded starch by day-5, lowest a* value (-0,44), and higher disease severity of 4.17. Uncoated bananas showed 15.25% weight loss, completely degraded starch by day five, and the highest disease severity (5.00). These findings indicate that the spray application of chitosan is more effective than dipping in maintaining banana quality during storage and supports its practical application in commercial postharvest handling.